Investigation of the elimination kinetics of low and middle molecular weight uremic markers during hemodialysis treatment with the optoelectronic multispectral sensor. (December 2020) - Konoplev, G A; Stepanova, O S; Zemchenkov, G A; Korsakov, V; Kuznetsov, A; Frorip, A
Abstract: The elimination kinetics of conventional low-molecular weight uremic markers and advanced glycation end products (AGE products), which are considered as a possible middle molecular weight marker of uraemia in hemodialysis (HD) patients, was investigated by direct ultraviolet (UV) absorption spectroscopy of waste dialysis fluid. Light emitting diodes (LED) were exploited as quasi-monochromatic light sources in the deep UV spectral region for measuring optical transmission at the wavelengths 285 nm (the maximum of uric acid UV absorption) and 365 nm (the maximum of AGE absorption band). Optical absorption of waste dialysate was monitored during multiple HD sessions for a group of patients; the double-pool model of elimination kinetics was used for the curve fitting and approximation. It was revealed that kinetic behaviour of AGE products is almost not different comparing with uric acid and other conventional clinically proved uremic markers.